CONSTRUCTING A POLITICAL LEGACY IN THE NUSANTARA CAPITAL CITY DEVELOPMENT UNDER JOKO WIDODO’S PRESIDENCY (Pena Cendekia Insani, 2026)
The development of the Nusantara Capital City (IKN) is a major national initiative heavily laden with political dimensions regarding power distribution and legitimation. This study aims to examine how the IKN development project is utilized as a vehicle to construct, reinforce, and legitimize the political legacy during President Joko Widodo’s precidency from 2019 to 2024. The research employs a qualitative method utilizing Norman Fairclough’s (1995) Critical Discourse Analysis (CDA) approach to unearth the power relations underlying the texts and contexts of the discourse. The findings indicate that the government massively produces and reproduces narratives such as Indonesia-centric developmental equity, a smart-green city, and the foundation for the